Triazolyl tryptoline derivatives as β-secretase inhibitors - Jutamas Jiaranaikulwanitch (2018)
Tryptoline, a core structure of ochrolifuanine E, which is a hit compound from virtual screening of the Thai herbal database against BACE1 was used as a scaffold for the design of BACE1 inhibitors. The tryptoline was linked with different side chains by 1,2,3-triazole ring readily synthesized by catalytic azide-alkyne cycloaddition reactions. Twenty two triazolyl tryptoline derivatives were synthesized and screened for the inhibitory action against BACE1. JJCA-140 was the most potent inhibitor (IC50= 1.49 μM) and was 100 times more selective for BACE1 than for Cat-D. © 2010 Elsevier Ltd. All rights reserved.